Joining of Aluminum Alloy AA7075 and Titanium Alloy Ti-6Al-4V through a Friction Stir Welding-Based Process - Francisco Dias; Gonçalo Cipriano; Arménio N. Correia; Daniel F. O. Braga; Pedro Moreira; Virgínia Infante (Metals, 2023)
Combining dissimilar parts has become imperative for developing the structures based on lightweight materials, such as metal alloys, polymers or polymer matrix composites, and this has become one of the solutions to reverse the current trend of CO2 emissions in the transport sector. However, given the usual property disparities, joining dissimilar materials in multi-material and multi-purpose structures raises new engineering challenges. Advanced joining processes, such as friction stir welding (FSW), have emerged and have been applied across several sectors as a promising alternative to conventional joining processes, such as mechanical fastening or adhesive bonding. In the present work, and in order to avoid the development of intermetallic compounds (IMCs), a different approach from the conventional technique of friction stir welding was applied to the production of dissimilar overlapping joints. These dissimilar joints were fabricated using a high strength aluminum alloy (AA7075-T651) and a titanium alloy (Ti-6Al-4V), both materials widely used in automotive, aeronautics and space industries. To perform a systematic investigation, the Taguchi method was used to determine the process parameter combinations to enable the fabrication of this type of dissimilar joints. The joints were subjected to quasi-static tensile shear tests to assess their mechanical performance and were compared to conventionally riveted joints in different configurations, namely, single and double connection points. The joints produced by the FSW based method showed higher mechanical performance. To assess the local properties, some of the fractured regions of the joints were subjected to hardness assessments, revealing no significant change in the hardness in the tested areas. Finally, a statistical study was performed to analyze the main effects and interactions of the process parameters, to identify their influences on the mechanical performance of the joints.